2009
DOI: 10.1590/s0074-02762009000700019
|View full text |Cite
|
Sign up to set email alerts
|

Tracing lineage by phenotypic and genotypic markers in Salmonella enterica subsp. enterica serovar 1,4,[5],12:i:- and Salmonella Typhimurium isolated in state of São Paulo, Brazil

Abstract: Fifty-three Salmonella 1,4,[5],

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
0
9
0
5
Order By: Relevance
“…Typhimurium. The literature confirmed that DT2 and DT99 have never been associated with monophasic isolates (Echeita et al., 2001; Tavechio et al., 2009; EFSA, 2010. ; Hauser et al., 2010), whereas a S .…”
Section: Discussionmentioning
confidence: 88%
“…Typhimurium. The literature confirmed that DT2 and DT99 have never been associated with monophasic isolates (Echeita et al., 2001; Tavechio et al., 2009; EFSA, 2010. ; Hauser et al., 2010), whereas a S .…”
Section: Discussionmentioning
confidence: 88%
“…Además de Estados Unidos, en países del resto de América como Canadá y Brasil, la STVM también se encuentra en los cinco primeros lugares de aislamientos provenientes de muestras de humanos, en tanto que el 100 % de los aislamientos de animales de engorde en estos países corresponde a dicha variante (33,34), En Argentina solo existe un reporte reciente de su presencia en granjas de cerdos (35). En Colombia, en solo cinco años desde su primera identificación en aislamientos clínicos, la variante monofásica se ubicó en el cuarto lugar de la vigilancia, lo que evidencia su capacidad de diseminación (14).…”
Section: Discussionunclassified
“…S. I. 4, [5],12:i:-has been responsible for an increasing number of foodborne outbreaks, attributed to pigs and pork products and frequently associated with the emergence of the multidrug-resistant phenotype 21,23 .…”
Section: Distribution Of Salmonella Serotypes From Human Infectionsmentioning
confidence: 99%